Assessment of indoor air quality at an electronic cigarette (Vaping) convention. (November 2018) - Chen, Rui; Aherrera, Angela; Isichei, Chineye; Olmedo, Pablo; Jarmul, Stephanie; Cohen, Joanna; Navas-Acien, Ana; Rule, Ana
Abstract E-cigarette (vaping) conventions are public events promoting electronic cigarettes, in which indoor use of e-cigarettes is allowed. The large concentration of people using e-cigarettes and poor air ventilation can result in indoor air pollution. In order to estimate this worst-case exposure to e-cigarettes, we evaluated indoor air quality in a vaping convention in Maryland (MD), USA. Real-time concentrations of particulate matter (PM10 ) and real-time total volatile organic compounds (TVOCs), CO2 and NO2 concentrations were measured. Integrated samples of air nicotine and PM10 concentrations were also collected. The number of attendees was estimated to range from 75 to 600 at any single observation time. The estimated 24-h time-weighted average (TWA) PM10 was 1800 μg/m3, 12-fold higher than the EPA 24-h regulation (150 μg/m3 ). Median (range) indoor TVOCs concentration was 0.13 (0.04–0.3) ppm. PM10 and TVOC concentrations were highly correlated with CO2 concentrations, indicating the high number of people using e-cigarettes and poor indoor air quality. Air nicotine concentration was 125 μg/m3, equivalent to concentrations measured in bars and nightclubs. E-cigarette aerosol in a vaping convention that congregates many e-cigarette users is a major source of PM10, air nicotine and VOCs, impairing indoor air quality. These findings also raise occupational concerns for e-cigarette vendors and other venue staff workers.